A randomised study to compare Cu T 380A and Cu 375 as postpartum intrauterine contraceptive method - Dolly Chawla; Attulori Loukya; Charvi Chugh; Shikha Chadha (New Indian Journal of OBGYN)
Objectives: To compare the efficacy of Cu T 380 A and Cu 375 in terms of failure rates. To compare side effects, expulsion rates, acceptability and problems experienced while using the two intrauterine devices. Method: A randomized case control study was conducted on 320 postpartum women willing for PPIUCD insertion after normal vaginal delivery.160 women each group A and B were inserted with IUCD Cu T 380A and Cu 375 respectively. Follow up visits were done at 6 weeks, 6 months and 1 year. Observations were recorded and comparative analysis was done. Results: Acceptability of PPIUCD was very high in both groups, 71.25 % (n=114) in group A and 79.38 % (n=127) in Group B. Menorrhagia was reported amongst 6.52% women in group A and 11% in group B at the end of 1 year of follow up. In group A, 22 (15.28%) women and 18 (12.85%) women in group B had expulsion of IUCD over one year. IUCD removal was rate was 30 (18.75%) women in group A and 23 (14.38%) in group B. Overall continuation rate at one year was 57.5% in group A and 62.5% in group B (P value=0.59). No failure was reported. Conclusion: Cu T 380 A and Cu 375 were found to be similar in terms of efficacy, complications and expulsion rates. Overall satisfaction was higher for Cu 375 than Cu 380A.